2020
DOI: 10.46281/ijfb.v4i1.633
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foreign Exchange Reserve, Exchange Rate and Crude Oil Price on Dhaka Stock Exchange Index: An Empirical Evidence from Vector Error Correction Model

Abstract: The supreme thrust of the present analysis is to explore the influences of foreign exchange reserve, exchange rate, and crude oil price on the stock index of the Dhaka stock exchange (DSE) of Bangladesh. Moreover, this study evaluates the identity of any unpremeditated relationship among the variables from the viewpoint of an emerging country like Bangladesh. Through using monthly time-series data, this study tries to discover the evidence of a long-run affiliation among the variables by using Johansen’s Coint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…While the findings obtained from the study obtained similar findings with the studies performed by Dursun and Özcan (2019), Le and Chang (2011) ve Zhang et al (2020), Golder et al (2020) and Wanat et al (2015) found contradictory findings with the studies conducted. However, the effect of the variables used in the studies and the length of the data set on the results should be analyzed separately.…”
Section: Model I →supporting
confidence: 72%
“…While the findings obtained from the study obtained similar findings with the studies performed by Dursun and Özcan (2019), Le and Chang (2011) ve Zhang et al (2020), Golder et al (2020) and Wanat et al (2015) found contradictory findings with the studies conducted. However, the effect of the variables used in the studies and the length of the data set on the results should be analyzed separately.…”
Section: Model I →supporting
confidence: 72%
“…In the causality study, a one-way causality relationship from stock market indexes to oil prices and from natural gas prices to stock market indexes was determined. Golder et al (2020) could not find a causality relationship between crude oil prices and the stock market index in their study. In another study, Le and Chang (2011) found that the Japanese stock market reacted positively to the change in oil prices.…”
Section: Literature Reviewmentioning
confidence: 73%
“…It is crucial in research to select a suitable lag length of the series before starting with the ARDL technique, as long-run relationship of variables relies on optimum lag size [39]. Introducing excess lags or applying fewer lags almost certainly omits factual information from the model and may result in inaccurate model estimates [40]. Considering this fact, this study determines lag size using the Akaike Information Criterion (AIC).…”
Section: Resultsmentioning
confidence: 99%